2011
DOI: 10.1123/jce.4.3.76
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Way Five Women Coaches Develop: Their Primary and Secondary Socialization

Abstract: Using Jarvis ' (2006) psychosocial perspective of human learning, we explore how the career choices and the subsequent coaching approaches of five Canadian women coaches have been influenced by their primary and secondary socialization. A content analysis was performed to identify how coaches learned in their primary socialization with their family, and in their secondary socialization at school and in their sport experiences. The findings indicate that the learning situations in their primary and secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…4 In this experience with mentors during the practice, studies have confirmed that it becomes one of the main factors that lead coaches to real learning. 25,32 Scaglia 38 highlights that this does not mean copying, following or idealizing a professional, but studying in a rational and methodical way to understand his philosophy and to consider what is positive.…”
Section: Learning From the Discussion And Observations Of Other Coachesmentioning
confidence: 99%
See 3 more Smart Citations
“…4 In this experience with mentors during the practice, studies have confirmed that it becomes one of the main factors that lead coaches to real learning. 25,32 Scaglia 38 highlights that this does not mean copying, following or idealizing a professional, but studying in a rational and methodical way to understand his philosophy and to consider what is positive.…”
Section: Learning From the Discussion And Observations Of Other Coachesmentioning
confidence: 99%
“…24 To guide the responses, the interviewer used a pre-established script in the interaction with the participants. In this paper, we present an interview script that was constructed from specific literature 7,13,[25][26][27] and improved with a pilot study of three coaches of young players, in a process conducted by two PhD with more than 10 years of qualitative research experience, and a Master Candidate.…”
Section: Patterns In Sscgmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as coaching contexts change are important for coaches to consider when problem solving, it should make sense that there is no fully pre-packaged, correct answer regarding many components in S&C coaching (21). Recent research in coach education also demonstrates how each coach's primary and secondary socialization influences his or her coaching practices (3). This means that a coach's identity and experiences influence what he does and how he understands the world.…”
mentioning
confidence: 99%